THE OBESITY AND THE PROBLEMATIZATION OF CORPULENCE IN THE MIDDLE AGES (Fiep Bulletin - online, 2012)
This article's aim was analyse the historical sources of medieval's obesity statements refer by some authors. The main focus was about the statement that the concept already existed in the Middle Age and the condition was considerated a pathology, as today. The methodology applied was the historiography. Based on the documents, the conclusions were that the concept didn't exist and the problematization relapse on the act of overeating, wich was seen as a sin. Beside, analysis of the material wasn't found a patological problematization of corporal fat, as those authors suggest. It follows, so, that the statements about medieval's obesity came of historical and linguistics descontextualization.
Keywords: obesity; history; pathology